Nutritive value of elephant grass obtained at different cutting ages in the transitional climate and soil of savae/forest of the state of Roraima - da Silva Peixoto, Anderson; de Jesus dos Santos, Edileusa (Seven Editora, 2023)
The objective of this study was to evaluate the nutritive value of elephant grass obtained at different cutting ages, being cultivated in the transition region of the state of Roraima, leaving the forest of the South of the state to the north savannah, from chemical-bromatological analyses and in situ  degradability.  For this purpose, a randomized block design   was used, being evaluated  at five  cutting ages (35, 45, 55, 65, and 75 days of cutting age), each with 4 replications. Weeding scans already established  on campus were used.  After collection on the  predetermined days, the samples were pre-seed for subsequent chemical-bromatological analyses (DM, MM, Mo EE, PB and EDF) and in situ degradability of  DM and  THD were performed. A significant difference (P